Magnesium Oxide Nanoparticles: A New Frontier in Antiviral Therapy Against Herpes Simplex Virus Type 1 - Abdulhussain Kadhim Jwaziri; Zahra Salavatiha; Seyed Jalal Kiani; Pegah Khales; Masoud Vazirzadeh; Ahmad Tavakoli (Advances in Virology)
Conclusion: MgONPs can exert their inhibitory effects on HSV-1 in a dose-dependent manner, both directly and through interfering with the replication cycle of the virus.